The prevalence and comorbidity of Attention-Deficit-Hyperactivity-Disorder in learners with Specific Learning Disorder (Developmental Dyslexia) in a South African practice - Geertsema, Salome (University of Pretoria, 2022)
Dissertation (MA (General))--University of Pretoria, 2021.